THE EFFECT OF COMMITMENTS AND ORGANIZATION TRANSFORMATIONAL LEADERSHIP ON TEACHER ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2016)
Abstract.quantitative correlation study took 18teachersampling junior high schoolThoriqotunNajahSingosariMalang.The data collection technique using a questionnaire that has been tested the validity and reliability test. Data analysis technique used isAnalisia, multiple linear regression correlation  the results obtained Fcount = 86.818 is greater than the Ftable: 0,05; 2; 18 by dk v1 = 2 and v2 = 18, the score of 3.554557 or with a significance level of 0.000 (p <0.05), the regression model, namely variable transformational leadership and organizational commitment together can be used to predict the organizational citizenship behavior Master Junior ThoriqotunNajahSingosariMalang..